Analisa Efektivitas Media Dalam Meningkatkan Kesiapsiagaan Berbasis Representatif Media: Struart Hall - Yensi Purwanti; Dyah Mustika Putri; Kadita Syarifatul Aulia (Jurnal Insan Pendidikan dan Sosial Humaniora, 2023)
Knowing Indonesia's unique geographical conditions, various disaster risks have been discovered that will occur. This disaster risk is found in areas that have special conditions, one of which is the Pancer Beach area. Where conditions are close to the beach, various disaster risks definitely arise. That's why preparedness is needed for the surrounding community which is built on an understanding of early warning. Social media representation also plays an important role in the effectiveness of Early Warning System deployment. So research was conducted which aimed to analyze the effectiveness of social media representations used in increasing citizen readiness based on an early warning system. This research method uses a qualitative approach with data collection techniques in the form of in-depth interviews, observation and analysis of documents related to early warning systems. The research results show that the effectiveness of using the media to convey information to citizens is still lacking. This research also found several challenges in the implementation process. Residents who live on the coast and in remote parts of the village have different access to the internet or social media they use. Based on the final analysis, this research recommends strategies related to media collaboration with in-depth representation regarding the dissemination of information and overall participation. So it can increase effectiveness in the process.